2023
DOI: 10.1063/5.0098680
|View full text |Cite
|
Sign up to set email alerts
|

Broadband electromagnetic emission via mode conversion mediated by stimulated Raman scattering in inhomogeneous plasma

Abstract: Electromagnetic emission via linear mode conversion from electron plasma waves (EPWs) excited by stimulated Raman scattering (SRS) of an incident laser pulse in inhomogeneous plasma is investigated theoretically and numerically. It is found that the mode conversion can occur naturally in underdense plasma region below the quarter critical density provided that EPWs are generated due to the development of backward SRS when the laser pulse is incident at certain angle with the plasma density gradient. The produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…To understand the hot electron generation via SRS in an inhomogeneous plasma, it is necessary to know how EPWs propagate and evolve. It has been shown before, when an EPW is excited in inhomogeneous plasma, its local wave number will change with time [30]. It is assumed that BSRS instability generates a large-amplitude Langmuir wave everywhere in space, which then evolves in time.…”
Section: Propagation Of An Epw In Inhomogeneous Plasma and The Change...mentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the hot electron generation via SRS in an inhomogeneous plasma, it is necessary to know how EPWs propagate and evolve. It has been shown before, when an EPW is excited in inhomogeneous plasma, its local wave number will change with time [30]. It is assumed that BSRS instability generates a large-amplitude Langmuir wave everywhere in space, which then evolves in time.…”
Section: Propagation Of An Epw In Inhomogeneous Plasma and The Change...mentioning
confidence: 99%
“…On the other hand, for the EPW excited by SRS propagating in an inhomogeneous plasma, its wavenumber and phase velocity change with space and time [28][29][30], which may have important effects on electron trapping and acceleration. For example, for absolute SRS developed near the quarter critical density in an inhomogeneous plasma, it is shown that when the excited EPW propagates towards the turning point, some trapped electrons can be further accelerated by the primary EPWs as its phase velocity increases [31].…”
Section: Introductionmentioning
confidence: 99%